Hotel Artemis [videorecording (DVD)] - Pearce, Drew, 1975-; Pearce, Drew, 1975-; Foster, Jodie; Brown, Sterling K.; Goldblum, Jeff, 1952- (Global Road/Universal Pictures Home Entertainment, 2018)
In the midst of a riot-torn Los Angeles, a mysterious woman named the Nurse runs a secret emergency room and hospital for criminals.